The Concept of Maqashid Sharia In Preventing The Negative Impact of Gold Amalgamation Activities On The Community of Hutabargot Sub-District, Mandailing Natal District - Munawar, Zain; Sukiati, Sukiati; Syahmedi Siregar, Ramadhan (Journal of Law, Politic and Humanities, 2024)
This research examines the application of the Maqashid Syariah concept in an effort to prevent the negative impact of gold amalgamation activities on the people of Hutabargot Subdistrict, Mandailing Natal Regency. Maqashid Sharia, which consists of five main objectives-Hifz al-Din (protection of religion), Hifz al-Nafs (protection of the soul), Hifz al-Aql (protection of the intellect), Hifz al-Nasl (protection of offspring), and Hifz al-Mal (protection of property)-provides a comprehensive framework for addressing the environmental and health problems caused by gold mining practices. This research uses a qualitative approach with a case study method to analyze the impact of gold amalgamation on public health and the environment and how Maqashid Sharia can be applied as a solution. The results show that the application of Maqashid Sharia can mitigate the negative impacts of gold amalgamation through various measures, such as the application of environmentally friendly technology, strict regulations, and increased public awareness and education regarding safe and sustainable mining practices. In addition, active participation from the government, religious institutions and local communities is crucial in the implementation of this concept. The government needs to supervise and regulate mining practices more effectively, while religious institutions can help raise awareness of the importance of protecting health and the environment in accordance with Islamic teachings. Local communities should also be actively involved through education and training on responsible mining practices. Thus, the application of Maqashid Sharia is expected to create a balance between the economic benefits of gold mining and the protection of public health and environmental sustainability, thereby achieving long-term sustainability.